New Metal Complexes with AZO ligand; Synthesis, Spectral Characterisation and Biological Evaluation - Ahmed Ibrahim Ahmed, Enaam Ismail Yousif (Pakistan Journal of Medical & Health Sciences, 2022)
The new Azo ligand and its metal complexes have been prepared and characterized The reaction of 4-nitroaniline and 2-hydroxy-1-naphthaldehyde in a 1:1 mole ratio resulted in the synthesis of ((E)-2-hydroxy-3-((4-nitrophenyl) diazenyl)-1-naphthaldehyde) (HL). The separation of monomeric complexes was accomplished by reacting ((E)-2-hydroxy-3-((4-nitrophenyl)diazenyl)-1-naphthaldehyde) (HL) with Cr, Mn II, Co II, Ni II, and Cu II metal ions in a mole ratio of 2:1 (L: M). Elemental microanalysis, magnetic susceptibility, conductance, FT-IR, electronic spectra, and 1HNMR, 13C-NMR, and mass spectra were among the analytical and spectroscopic techniques used to describe the products. Based on the data collected during the characterization process, six coordinates were determined. The ligand and its complexes were tested against certain bacteria and fungi. The findings acquired suggested that the metal complexes are more active against a variety of organisms have been studied as compared to the free ligand. Keywords: ((E)-2-hydroxy-3-((4-nitrophenyl) diazenyl)-1-naphthaldehyde); Azo ligand; Candida and Rhizopus porium; 2-hydroxy-1-naphthaldehyde; Metal Complexes.